Exploration and Inventory of Banjar Etnochemistry as a Learning Source in Indonesia Senior High School Chemistry Context - Ratna Kartika Irawati; Ardian Trio Wicaksono; Salamiyah Salamiyah; Eko Wahyu Nur Sofianto; Tommy Tanu Wijaya (Jurnal Tadris Kimiya, 2023)
Ethnochemistry is the study of chemical practices by specific cultural groups that are used for activities following the ideology of the community, including the Banjarese community. Banjar ethnochemistry can be integrated into science learning, especially for Indonesia’s senior high school chemistry learning context. This study aims to analyze the results of exploring the local wisdom of the Banjarese community, which is included in ethnochemistry, and to take an inventory of Banjar ethnochemical knowledge as a source of Indonesia senior high school chemistry learning. The study uses an exploratory qualitative approach with ethnographic methods. The subjects in this research are community leaders and academics who understand Banjar ethnochemistry. Data collection techniques used interviews, observation, and documentation. The results of the Banjar ethnochemical exploration include Banjar soup, sasirangan, basungu, rub ash, batimung, sepat dry fish, diamond, tanggui, tapai Gambut, laduman, kelakai, ironwood, ironwood hair oil, fish pentol, selangat shredded fish, Mangurak wells, mandai, and lahang ice. An inventory of Banjar ethnochemical knowledge that can be used as a source for Indonesia senior high school chemistry learning consists of acids and bases, chemistry and its scope, alkane derivatives, macromolecules, elemental chemistry, and colligative properties of solutions.